PEDAGOGICAL SIGNIFICANCE OF VISUAL-PERCEPTUAL EXERCISES (CONNECT-THE-DOTS AND SEARCH ACTIVITIES) IN DEVELOPING WRITTEN SPEECH AMONG PRIMARY SCHOOL STUDENTS - Shukurova Dilfuza Rakhmatovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This study investigates the pedagogical significance of visual-perceptual exercises, specifically connect-the-dots and search activities, in developing written speech among primary school students. The research highlights how these activities contribute to the enhancement of visual perception, attention, memory, and graphomotor coordination, which are essential components of early writing skills. It is emphasized that such exercises provide a structured and engaging approach to handwriting preparation by improving children’s ability to recognize patterns, control hand movements, and differentiate visual information. The findings suggest that integrating visual-perceptual tasks into early literacy instruction significantly improves students’ writing accuracy, fluency, and overall readiness for formal written communication.